Comparação entre avaliação objetiva e subjetiva do comportamento sedentário de pessoas idosas brasileiras da comunidade: um estudo transversal - Berto, Nathalia Leite (Universidade Federal de São Carlos, 2025)
Introduction: Sedentary behavior (SB) is defined as a set of activities performed while awake in a sitting or lying position with an energy expenditure ≤ 1.5 METs. It is an indicator of mortality and is associated with various health risks, such as chronic diseases and functional decline in the older adults. Given its significant impact, accurately assessing sedentary behavior is crucial. Objective: To compare the objective and subjective assessment of SB in Brazilian older adults in the community and to analyze which activities are most performed in SB by this population. Methods: This is a cross-sectional study. Participants were older adults ≥ 60 years, members of the "Revitalização Geriátrica" extension project. Objective analysis was performed using accelerometry, considered the gold standard for SB assessment, and subjective analysis was performed using the LASA-SBQ questionnaire. The questionnaire was administered on the same day that the accelerometer was attached to the participant, which was removed after 7 days. Data collection occurred during August and September 2021. Data analysis: Data normality was tested using the Shapiro-Wilk test. To compare the objectively and subjectively assessed SB, the Wilcoxon test was used, according to normality assumptions. Spearman's test was used to verify the correlation between SB variables. A significance level of 5% was adopted and the analysis was performed using SPSS 2.0 software. Results: No statistical difference was found between the objective and subjective assessment variables of SB, however, a significant, positive, and weak correlation was observed (r = 0.319), indicating that the variables cannot present the same behavior consistently and therefore, one assessment method cannot replace the other. The analysis of the most performed activities in SB showed that watching television was the most frequent, followed by talking on the phone, listening to music, and engaging in hobbies. Conclusion: The results did not identify statistical differences between the objective and subjective assessments of SB, but the weak correlation indicates that the methods are not consistent with each other. Therefore, one method cannot replace the other. This reinforces the importance of raising awareness among the older adults population about their SB habits to promote more effective interventions.
Comparison between objective and subjective assessment of sedentary behavior in community-dwelling Brazilian older adults: a cross-sectional study
Keywords: Pessoas idosas; Comportamento sedentário; Avaliação; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL